The impact of the COVID-19 pandemic on child protection system referrals and responses in Colorado, USA - Brown, Samantha M. (Child maltreatment, 2022)
Although the coronavirus disease 2019 (COVID-19) has amplified risk factors known to increase children’s vulnerability to abuse and neglect, emerging evidence suggests declines in maltreatment reporting and responding following COVID-19 social distancing protocols in the United States. Using statewide administrative data, this study builds on the current state of knowledge to better understand the volume of child protection system (CPS) referrals and responses in Colorado, USA before and during the early phase of the COVID-19 pandemic and to determine whether there were differences in referral and response rates by case characteristics. Results indicated an overall decline in referrals and responses during COVID-19 when compared to the previous year. Declines were specific to case characteristics, such as reporter and maltreatment type. Implications regarding the impact of the COVID-19 pandemic on child maltreatment reporting and CPS response are discussed.